Bridging max graph neural networks and datalog with negation - Tena Cucala, D; Cuenca Grau, B (IJCAI Organization, 2024)
We consider a general class of data transformations based on Graph Neural Networks (GNNs), which can be used for a wide variety of tasks. An important question in this setting is characterising the expressive power of these transformations in terms of a suitable logic-based language. From a practical perspective, the correspondence of a GNN with a logical theory can be exploited for explaining the model’s predictions symbolically. In this paper, we introduce a broad family of GNN-based transformations which can be characterised using Datalog programs with negation-as-failure, which can be computed from the GNNs after training. This generalises existing approaches based on positive programs by enabling the learning of nonmonotonic transformations. We show empirically that these GNNs offer good performance for knowledge graph completion tasks, and that we can efficiently extract programs for explaining individual predictions.